Penataan Kampung Nelayan Untia Berbasis Mitigasi Bencana - Naing, Naidah; Amalia, Ria Rezky (DPW FORSILADI SULSEL, 2024)
The condition of fishing settlements in the coastal area of Makassar City, particularly Kampung Nelayan Untia, reflects challenges similar to those faced in various urban areas across Indonesia. Kampung Untia, constructed to accommodate fishermen relocated from Lae-Lae Island due to the development of the island as a tourism area, is located only 50 meters from the high tide line, posing significant risks to residents' safety. Although the government, through the Ministry of Public Works and Housing (PUPR), has planned the development of a 10-hectare area with basic infrastructure such as clean water supply and sanitation systems, its implementation remains suboptimal. The settlement also fails to meet the standards set by the Indonesian Minister of Public Housing Regulation No. 15/Permen/M/2006, regarding essential facilities such as docks and boat moorings. Field observations reveal that the area is vulnerable to natural disasters such as tornadoes, seawater intrusion, coastal erosion, and ground fissures, indicating non-compliance with Presidential Regulation No. 51 of 2016 on coastal area protection. This study employs a qualitative approach using primary data from field surveys and interviews, as well as secondary data from documents and relevant journals. The findings highlight the need for a disaster mitigation approach in the development of Kampung Nelayan Untia to create a safe and sustainable coastal settlement.